2019
DOI: 10.18203/issn.2454-5929.ijohns20192070
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pre-operative sino-nasal outcome test- 22 scores as a predictor of outcome in patients undergoing functional endoscopic sinus surgery for chronic rhinosinusitis

Abstract: <p class="abstract"><strong>Background:</strong> Numerous factors are to be considered when offering FESS as a treatment for patients with chronic rhinosinusitis (CRS) who have failed conservative medical treatment. The objective is to evaluate the sino-nasal outcome test (SNOT-22) and other patient demographic characteristics as predictors of postsurgical improvement in patients with CRS.</p><p class="abstract"><strong>Methods:</strong> Consecutive adult subjects pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…CRS is a debilitating condition with significant economic impact. 3 Most authors have shown that FESS is effective in treating recalcitrant CRS. [4][5][6] Assessment of outcome following FESS includes both endoscopic and quality of life assessment.…”
Section: Discussionmentioning
confidence: 99%
“…CRS is a debilitating condition with significant economic impact. 3 Most authors have shown that FESS is effective in treating recalcitrant CRS. [4][5][6] Assessment of outcome following FESS includes both endoscopic and quality of life assessment.…”
Section: Discussionmentioning
confidence: 99%